Abscisic acid activates desiccation tolerance responses in intertidal seaweed Neoporphyra haitanensis - Caixia Zhang; Juanjuan Chen; Rui Yang; Qijun Luo; Tiegan Wang; Peng Zhang; Haimin Chen (Frontiers in Marine Science, 2022)
Intertidal macroalgae have adapted to deal with environmental stresses, in particular desiccation. The phytohormone abscisic acid (ABA) plays an important role in the regulation of a suite of critical responses in plants, including desiccation tolerance. The red alga Neoporphyra haitanensis contains a high level of ABA, but its mechanism of action in N. haitanensis is unknown. In this study, the effect of ABA treatment on the relative water content of thalli during the dehydration-rehydration cycle was evaluated and it was identified that ABA treatment resulted in decreased thalli water loss and an accelerated rehydration process. The effects of addition of ABA upon the activation of antioxidant responses, photosynthetic parameters and gene transcription profiles of N. haitanensis were also evaluated. The results revealed that exogenous ABA regulated the activation of the antioxidant system, including by increasing the activity of antioxidant enzymes, increasing the concentrations of ascorbic acid (AsA) and glutathione (GSH), as well as upregulating the expression of genes encoding antioxidant enzymes and enzymes that synthesize AsA and GSH. ABA treatment also inhibited photosynthesis by reducing light capture and down-regulating the Calvin cycle to save energy; ABA supplementation further simultaneously activated repair mechanisms to avoid excessive DNA and protein damage. The results presented herein demonstrate that ABA plays a crucial role in the regulation of stress tolerance in seaweeds, which may be of great importance when examining the adaptation of this organism to the intertidal environment.

A study on the infection status and transmission of avian leukosis virus subgroup J in Hy-line brown roosters - Fanfeng Meng; Qiuchen Li; Rui Han; Guanlong Xu; Xintao Gao; Fubing Luo; Guangnian Shen; Xiaodong Liu; Zhifang Zhang; Peng Zhao; Guozhong Zhang (Archives of Virology, 2022)

Targeting iNOS Alleviates Early Brain Injury After Experimental Subarachnoid Hemorrhage via Promoting Ferroptosis of M1 Microglia and Reducing Neuroinflammation - Wenhao Qu; Ying Cheng; Wei Peng; Yan Wu; Tongyu Rui; Chengliang Luo; Jian Zhang (Molecular Neurobiology, 2022)